Lichens and lichenicolous fungi of Khortytsia Island (Ukraine) (CHORNOMORSKI BOTANICAL JOURNAL, 2020)
80 species of lichens and 12 species of lichenicolous fungi were found on Khortytsia Island. The lichen Verrucaria fusconigrescens is for the first time reported for the continental part of Ukraine. Lichens Acarospora insolata, Bacidia fuscoviridis, Caloplaca chlorina, C. soralifera, C. xerica, Dermatocarpon miniatum, Lecanora argopholis, L. orosthea, L. swartzii, Lobothallia alphoplaca, Monerolechia badia, Rhizocarpon lecanorinum, Xanthocarpia crenulatella, Xanthoparmelia loxodes and lichenicolous fungi Abrothallus caerulescens, Lichenostigma elongatum, Marchandiomyces corallinus, Polycoccum pulvinatum, Stigmidium xanthoparmeliarum, Zwackhiomyces lithoiceae are reported for first time for Zaporizhzhia Region. Melanelixia fuliginosa, Protoparmelia badia and Evernia mesomorpha were erroneously reported for Khortytsia Island and therefore should be excluded from the list of species. Of the recorded lichens, two species, Lassalia pustulata and Xanthoparmelia camtschadalis, are included into the Red Data Book of Ukraine. Verrucaria fusconigrescens is a new host for Zwackhiomyces lithoiceae.
Keywords: Ukrainian crystalline shield, granite, Zaporizhzhia, Dnipro river.